-7n+4(2n-2)=-2(4+6n)

Simple and best practice solution for -7n+4(2n-2)=-2(4+6n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7n+4(2n-2)=-2(4+6n) equation:



-7n+4(2n-2)=-2(4+6n)
We move all terms to the left:
-7n+4(2n-2)-(-2(4+6n))=0
We add all the numbers together, and all the variables
-7n+4(2n-2)-(-2(6n+4))=0
We multiply parentheses
-7n+8n-(-2(6n+4))-8=0
We calculate terms in parentheses: -(-2(6n+4)), so:
-2(6n+4)
We multiply parentheses
-12n-8
Back to the equation:
-(-12n-8)
We add all the numbers together, and all the variables
n-(-12n-8)-8=0
We get rid of parentheses
n+12n+8-8=0
We add all the numbers together, and all the variables
13n=0
n=0/13
n=0

See similar equations:

| 9m+2m+3m-8m+4m=20 | | 5x-3x-16+18=78 | | 2(x+9)=2(x+7) | | −3/4x+5=−7 | | Xx5=-4 | | |2x=5|=11 | | 13w+11= | | 9c-1=4c-1 | | 7b-2b-3b+5b=7 | | 3x-(5x-6)=3x+(5x-7) | | 12x-60=4x+12 | | -6(r-1)+6=-(-6+6r)+6 | | 9x+34=160 | | 15h-14h=14 | | 24y-36=12() | | `19=2x+10` | | 75h=150 | | 4-6g=40 | | 5+2x+2x=2x=15 | | 5d+26=9d+2 | | 2x/3+7=-14 | | 6+2n=13 | | f/4+5=2 | | 15x-31-9x+11=180 | | -5+9d+2d=9+12d | | 4x+34+(3x)=90 | | 5a=7=4a | | -6(8v-1)=-8(7v+5)-2 | | –2n–16=4n+8 | | Y=-3/7x+5 | | 4m+20=12m-12 | | 4k^2+6k-15=3 |

Equations solver categories